Patriarchy and the Structure of Employment in Criminal Justice: Differences in the Experiences of Men and Women Working in the Legal Profession, Corrections, and Law Enforcement - Batton, Candice (2018)
Feminist scholars have long argued that patriarchy affects the structure and organization of society as well as the lived experiences of men and women. Although often referenced in discussions of gender differences in crime and justice, few have articulated more specifically the link between patriarchy and gender differences in the experiences of men and women as victims, offenders, or workers. We take up the challenge to theorize patriarchy and examine the extent to which it operates as an organizing principle with regard to employment in the criminal justice system. We consider differences in the representation of men and women working in the legal profession, corrections, and law enforcement, as well as the culture and structure of these workplace environments in the United States. We argue that patriarchy is a useful midlevel theoretical concept that helps explain both quantitative and qualitative gender differences in criminal justice work. This study complements the “doing gender” approach by focusing on gender at the institutional level, and describing how the culture and structure of the criminal justice system shape and constrain the experiences of individuals occupying social roles within it